EDUKASI TENTANG INTERVENSI NON-FARMAKOLOGIS DALAM MENGATASI NYERI MENSTRUASI PADA SISWI SMA NEGERI 7 PALU - Andi Saifah; Windu Unggun Cahya Jalu Putra; Murshidah Khairiyah; Mayu Sanlia Samadani; Anjar Kusuma Dewi (LP2M Universitas Hasanuddin, 2023)
Menstrual pain (dysmenorrhea) is a health problem for young women. It is estimated that 26% of SMA Negeri 7 Palu students experience menstrual pain, which results in numerous complaints and discomfort that interfere with daily activities. The purpose of the service is to provide knowledge and skills about nonpharmacological interventions in dealing with menstrual pain to SMA Negeri 7 Palu students. The service employed an educational method, including counselling about dysmenorrhea and the practice of abdominal stretching exercises and LI4 point acupressure. The service involved 80 participants who were separated into two groups. The first session consisted of students from class XI, and the second included students from class X. Evaluation of knowledge based on the pre-and post-test results and observation technique was used to evaluate abdominal stretching and acupressure skills. The outcomes of this service demonstrated that all activity accomplishments exceeded the success indicator target by 75%, specifically an increase in knowledge score of 88%. The abdominal stretching exercise skills score > 75 points, a total of 95%, with 22.5% in the sufficient category, 63.8% in the good category, and 8.8% in the excellent category. Acupressure skill achievement was divided into 32.5% moderate, 63.8% good, and 8.8% excellent. Participants are encouraged to regularly apply all the knowledge and abilities of nonpharmacological therapy they gain before or during menstruation, and they can assist peers in managing period discomfort. — Nyeri menstruasi (dismenore) merupakan salah satu masalah kesehatan remaja putri. Diprediksi 26% siswi SMA Negeri 7 Palu mengalami nyeri menstruasi dan menimbulkan berbagai keluhan dan ketidaknyaman yang berdampak pada aktivitas sehari-hari. Tujuan pengabdian adalah memberi pengetahuan dan keterampilan tentang intervensi non-farmakologis dalam mengatasi nyeri menstruasi pada siswi SMA Negeri 7 Palu. Metode pengabdian yang digunakan adalah edukasi meliputi penyuluhan tentang konsep dismenore dan praktik Latihan peregangan perut dan akupressur titik LI4. Peserta edukasi sebanyak 80 orang dibagi menjadi 2 kelompok yaitu sesi ke-1 pada siswi kelas XI dan sesi ke-2 pada siswi kelas X. Evaluasi pengetahuan berdasarkan hasil pre-post test dan tehnik observasi untuk penilaian keterampilan Latihan peregangan perut dan akupressur. Hasil pengabdian ini menunjukkan semua capaian kegiatan melebihi target indikator keberhasilan sebesar 75% yaitu peningkatan skor pengetahuan sebesar 88%, skor keterampilan latihan peregangan perut > skor 75 sejumlah 95% terdiri dari 22,5% kategori cukup, 63,8% kategori baik dan 8,8% sangat baik, dan capaian keterampilan akupressur terdiri dari 32,5% kategori cukup, 63,8% kategori baik dan 8,8% kategori baik sekali. Semua pengetahuan dan keterampilan terapi nonfarmakologis yang diperoleh peserta diharapkan diaplikasikan secara rutin menjelang atau saat menstruasi dan dapat membantu teman sebaya dalam mengatasi nyeri menstruasi.